2014
DOI: 10.1038/ncomms4599
|View full text |Cite
|
Sign up to set email alerts
|

Size evolution of highly amphiphilic macromolecular solution assemblies via a distinct bimodal pathway

Abstract: The solution self-assembly of macromolecular amphiphiles offers an efficient, bottom-up strategy for producing well--defined nanocarriers, with applications ranging from drug delivery to nanoreactors. Typically, the generation of uniform nanocarrier architecturesis controlled by processing methods that rely upon cosolvent mixtures. These preparation strategies hinge on the assumption that macromolecular solution nanostructures are kinetically stable following transfer from an organic/aqueous cosolvent into aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
76
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 64 publications
6
76
0
Order By: Relevance
“…Cryo-TEM experiments further demonstrated that mechanical agitation (stirring), in addition to TMB, is a requirement for producing these broadened micelle size distributions (Fig. 3e, j, o ), consistent with recent observations of complex polymer micelle size distributions in the presence of a co-solvent and solution agitation 34 . Associated structural transitions are illustrated schematically by the micelle packings in Fig.…”
Section: Resultssupporting
confidence: 89%
“…Cryo-TEM experiments further demonstrated that mechanical agitation (stirring), in addition to TMB, is a requirement for producing these broadened micelle size distributions (Fig. 3e, j, o ), consistent with recent observations of complex polymer micelle size distributions in the presence of a co-solvent and solution agitation 34 . Associated structural transitions are illustrated schematically by the micelle packings in Fig.…”
Section: Resultssupporting
confidence: 89%
“…79 2) The large hydrophilic-hydrophobic contrast represented by the high Flory-Huggins interaction parameter drives phase separation of the blocks and enables modulation of the reorganization kinetics based upon the presented solution conditions. [80][81][82][83] 3) The polymer is simple to synthesize in diverse laboratory settings by atom transfer radical polymerization (ATRP) using a chain extension from commercial PEO homopolymers. Different size PEO macroinitiators were synthesized by the esterification of commercial poly(ethylene glycol)methyl ether with 2-bromopropionic acid ( Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…1419 However, recent experiments have indicated that, even near equilibrium, fusion and fission processes may still occur. 2021 Fusion of micelles is also observed under flow conditions. 22 Far from equilibrium, theoretical work by Semenov and coworkers suggest that insertion and expulsion are prevalent; 23 however, Dormidontova et al have proposed that fusion and fission processes dominate.…”
Section: Introductionmentioning
confidence: 82%